Conflict of Abandoned Land Ownership in the Perspective of Agrarian Reform - Rico Binsar Manurung; Muhammad Yamin; Zaidar Zaidar (Ultimate Journal of Legal Studies, 2025)
This study examines land ownership conflicts over abandoned land in Hamlets I and V of Bandar Baru Village, Sibolangit District, Deli Serdang Regency, within the framework of Indonesian agrarian law. As a strategic resource, land management must be carried out in accordance with Article 33 paragraph (3) of the 1945 Constitution of the Republic of Indonesia and Law Number 5 of 1960 concerning Basic Agrarian Regulations. This study aims to analyze the factors causing land ownership conflicts and the legal resolution of disputes occurring in the area. The research employs an empirical juridical method with a qualitative approach. Data were obtained through library research and field studies in the form of structured interviews with the National Land Agency (BPN) of North Sumatra, legal counsel, and the communities of Hamlets I and V of Bandar Baru Village. The findings indicate that the land ownership conflict has not yet reached a definite legal resolution due to the absence of legal certainty regarding the status of the land and the indecisiveness of the National Land Agency in addressing overlapping land claims. This condition has triggered prolonged conflicts between the community and the government concerning land control and utilization. In addition, weak land administration and the lack of optimal coordination among government institutions have hindered the realization of legal certainty and agrarian justice. This study recommends a comprehensive, transparent, and equitable reorganization of land legal status through inventory and verification of land rights by involving communities that have historically controlled and utilized the land.